ANALISIS STANDAR PENILAIAN PENDIDIKAN DASAR - Alia Miranti Irzan, Putri; Pratama, Heldo; Lestari, Elviana; Ananda, Rizki; Nasrul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This article aims to analyze the Basic Education Assessment Standards regulated in Minister of National Education Regulation Number 23 of 2016. The method used is a documentation study of related policies, as well as a literature review of previous research. The results of the analysis show that basic education assessment standards are designed to ensure that the learning evaluation process can measure the achievement of graduate competencies holistically, covering the domains of attitudes, skills and knowledge. This assessment standard is an integral part of the National Education Standards as mandated by Law Number 20 of 2003 concerning the National Education System. The implementation of these assessment standards in elementary schools needs to be studied further so that they can be implemented effectively and in accordance with applicable regulations. Keywords: analysis, assessment standards and elementary schools